PENCABUTAN PENGADUAN OLEH ISTRI ATAS KEKERASAN DALAM RUMAH TANGGA YANG DILAKUKAN OLEH SUAMI - Siti Nurhasanah (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT Violence in the household is any action against someone, especially women, which results in physical, sexual, psychological, and/or neglect of the household, including threats to commit acts, coercion, or illegal deprivation of liberty within the scope of the household. The birth of Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT Law) is expected to be able to provide penalties for perpetrators of domestic violence.Some of the factors that cause someone to commit acts of violence in the household are 1. Economic factors 2. Behavior. 3. Jealousy, 4. Third parties, 5. Factor communication and so onGiven that there are still many cases of domestic violence that occur in Indonesia, especially in the city of Samarinda. In addition, it is also important to socialize the rights of victims, including the right to report, the right to receive protection.Keywords: Complaints, domestic violence (KDRT)